Utilizing the Advances in Digital Health Solutions to Manage Care in Cancer Patients - Charalambous, Andreas (My University, 2019)
In recent years, the clinical context for cancer has changed, and it is now characterized by extended survival rates and more diverse and complex cancer trajectories and symptomatology. The changes in the landscape of cancer care also include a shift towards the home setting or the outpatient setting with an increased amount of care being delivered at home or transferred to the patients themselves and their family caregivers. These changes have also impacted the type and amount of information required by the patients and their caregivers as well as the type of care needs that are to be addressed by health-care professionals. Finally, the transitions within the health-care setting might also create a caring gap that the patient is left to deal with independently or with minimal support. These changes have led to the emergence of innovative digital/technological solutions for supporting patients during their cancer care continuum.
Keywords: Digital health; eHealth; Information; mHealth; Smartphones; Symptom burden; Technology